A study on the factors that motivate cat owners to vaccinate their cats - Kumar, Ashitosh (2018)
Compliance to vaccination plays an important role in the control of infectious diseases in cats. Poor compliance to the recommended vaccination programme is among the reasons for the continual threat of preventable infectious diseases in cat populations. The benefits of routine vaccination are that the incidence of serious disease caused by highly pathogenic organisms, such as feline panleukopenia, can be reduced in populations in which widespread vaccination is practised. In developed countries it is estimated that only 30–50% of the cat population is vaccinated, and this could be significantly less in developing nations like Malaysia. Therefore, this study aimed to find out what are the factors that motivate owners to vaccinate their cats. The purpose of this study is to identify the common factors among owners that do and do not vaccinate their cats, and use this knowledge to construct a more directed and effective client education programme. 52 cat owners were sampled at the Universiti Veterinary Hospital for this study. They were interviewed using a questionnaire modified from a previous study on “pet health care”. The data was then tabulated in SPSS and analysed. Results showed that owners from the Bottom 40 % income group (B40) with household income of less than RM3900, were four times less likely (95 % CI: 0.057 – 0.980) to vaccinate their cats than the next income groups. Another significant factor identified was that owners who had more knowledge on vaccination practices were six times more likely (95 % CI: 0.029 – 0.763) to vaccinate their cats compared to owners with lesser knowledge on vaccination practices. Other relevant factors that influence compliance to vaccination includes number of people in the household, amount spent on the cat per month and owner‟s perception of the cat on whether it is a pet or part of the family. In conclusion, owner‟s income disposition and the knowledge of when to start vaccination, as well as ancillary cat ownership determinants, are important factors that motivate owners to vaccinate their cats. These factors should be considered in designing an effective and more directed client education programme to improve vaccination compliance among cat owners.